Agreement between blood draw techniques for assessing platelet activation by flow cytometry. (19th May 2019) - Welch, Emma L.; Crooks, Michael G.; Hart, Simon P.
Abstract: It is widely believed that assays of platelet activation are susceptible to preanalytical variables related to blood draw technique. We assessed platelet activation by whole blood flow cytometry and investigated the effects of: (1) drawing blood into vacuum tubes or manually aspirated syringes, and (2) discarding the first drawn blood sample (discard tube). Platelet P-selectin expression and platelet-monocyte complexes were measured by flow cytometry under both basal conditions and following stimulation with 0.1, 1, or 10 µM ADP. Bland-Altman plots demonstrated agreement between results for vacuum tube and syringe-aspirated samples with an a priori -defined clinically relevant agreement limit of 5%. Agreement of results was also observed between discard tube and second draw samples for both vacuum-driven and manually aspirated blood. We conclude that a vacuum tube or a manually-aspirated syringe can be used when assessing platelet activation by flow cytometry and that there is no need for a discard tube.